Deep Eutectic Solvent-Based Microwave-Assisted Extraction of Baicalin from Scutellaria baicalensis Georgi - Hui Wang; Xiaodi Ma; Qibin Cheng; Xiaoli Xi; Liwei Zhang (Journal of Chemistry)
Deep eutectic solvents (DESs) have attracted significant attention as green media for the extraction and separation of natural compounds from Chinese medicine. In this study, a hydrophobic DESs-based microwave-assisted extraction (MAE) was successfully used to efficiently extract baicalin from Scutellaria baicalensis Georgi. Firstly, DecA: N4444-Cl (DES-1 , molar ratio 1 : 2) was screened and selected as the most appropriate DES by comparing the extraction yield in different hydrophobic DESs. Based on the extraction yield of baicalin, response surface methodology (RSM) was employed to model and optimize the parameters (extraction temperature, liquid-solid ratio, and extraction time). Furthermore, the maximum yield of 106.96 mg·g−1 was achieved under optimum conditions in DES-containing aqueous solutions (33 vol% water content), which reached a similar level that was conducted using the pharmacopoeia procedure (104.94 mg·g−1). These results indicated that the proposed method is an excellent alternative for the extraction of baicalin.